How can a game-based toolkit for learning of mathematics cover even a prescriptive curricula? - Drobina, Ákos; Cselők, Dorottya; Csóka, E. Zora (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The research team of the Collage of Teacher Candidates at the University of Pécs has a research on the fi eld of renewal facilities on teaching and learning mathematics and science. Within this framework wecarroed out a study about a specifi c, existing and tested gamebased toolkit called MathterMinds on the aspect of the degree of thematization, in order to determine whether or to what extent it mobilizes the competence elements and disciplinary elements of mathematical competences prescribed by the currently operative framework curricula from 1st to 4th gardes in primary schools. The goal was to fi nd out whether a gamebased toolkit is capable of, and, if so, to what extent, to cover the requirements of a prescriptive framework curriculum.